Correction: Unexpected higher stabilisation of two classical antiaromatic frameworks with a ruthenium fragment compared to the osmium counterpart: origin probed by DFT calculations. Issue 7 (24th December 2015) - Wu, Jingjing; Hao, Yulei; An, Ke; Zhu, Jun
Abstract : Correction for 'Unexpected higher stabilisation of two classical antiaromatic frameworks with a ruthenium fragment compared to the osmium counterpart: origin probed by DFT calculations' by Jingjing Wu et al., Chem. Commun., 2016, 52, 272–275.